2003
DOI: 10.1007/s00122-002-1106-y
|View full text |Cite
|
Sign up to set email alerts
|

The heat-stable root-knot nematode resistance gene Mi-9 from Lycopersicon peruvianum is localized on the short arm of chromosome 6

Abstract: The tomato gene Mi-1 confers resistance to three species of root-knot nematodes, Meloidogyne spp. However, the resistance mediated by Mi-1 is inactive at soil temperatures above 28 degrees C. Previously, we identified and mapped a novel heat-stable nematode resistance gene from the wild species Lycopersicon peruvianum accession LA2157 on to chromosome 6. Here we report further characterization of this heat-stable resistance against three Mi-1-avirulent biotypes of Meloidogyne javanica, Meloidogyne arenaria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 24 publications
1
47
0
6
Order By: Relevance
“…The similar result was in Yaghoobi et al (1995) and Ammiraju et al (2003) experiment used the molecular marker method. The gene, which have designated Mi-3 and Mi-9 respectively, confers resistance against nematode strains that can't infect plants carrying Mi.Similar but not same in cotton, Ynturiet al (2004) experiment showed segregation ratio of 3:1 for susceptible and resistant in both F2 populations, suggesting a single recessive gene or one dominant and one recessive gene may be involved in controlling the resistance trait.…”
Section: Discussionsupporting
confidence: 76%
“…The similar result was in Yaghoobi et al (1995) and Ammiraju et al (2003) experiment used the molecular marker method. The gene, which have designated Mi-3 and Mi-9 respectively, confers resistance against nematode strains that can't infect plants carrying Mi.Similar but not same in cotton, Ynturiet al (2004) experiment showed segregation ratio of 3:1 for susceptible and resistant in both F2 populations, suggesting a single recessive gene or one dominant and one recessive gene may be involved in controlling the resistance trait.…”
Section: Discussionsupporting
confidence: 76%
“…For PCR analyses, DNA was isolated from leaflets using Wizard Genomic DNA purification kit (Promega) according to manufacturer's recommendation or as described in Ammiraju et al (2003). For DNA-blot analysis, DNA was isolated, restricted with EcoRV restriction enzyme, and DNA blots prepared according to Kaloshian et al (1998).…”
Section: Dna Isolation and Dna-blot Analysismentioning
confidence: 99%
“…Using a true F 2 segregating population, Mi-9 was mapped to chromosome 6 (Veremis et al, 1999). Mi-9 was further mapped to the short arm of chromosome 6 between markers CT119 and C8B, a similar genetic interval as Mi-1 (Ammiraju et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such an expansion of the analysis to include additional temperatures may be quite relevant, as previous research has demonstrated significant variation in the binding affinities of various proteins to their ligands with regard to environmental temperature [37], and nematodespecific FAR proteins have been shown to be heat-stable [13,20]. Given that plant-parasitic nematodes are much more prevalent during warmer seasons and in tropical climates [38][39][40] and that animal parasites would, by their nature, inhabit warmer environments, it seems possible that FAR studies conducted to date, at 20°C, may not accurately reflect the binding properties of this family of protein in vivo.…”
Section: Future Directions and Parasitic Fars As Targets In Drug Devementioning
confidence: 99%